Adoption Of Improved Dairy Farming Practices Among Tribal Community - Meena, H.R.; Meeena, K.L.; Fulzele , R.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present study was conducted in southern Rajasthan. A total of 200 respondents belong to tribal communities were selected purposively. The calculated ‘r’ value relationship with overall adoption of IDFPs indicated that socio-economic, socio-psychological and communication characteristics of the tribal dairy farmers were found to have positively significant relationship at one per cent level of probability with overall adoption of IDFPs.